2015
DOI: 10.1177/0194599815617130
|View full text |Cite
|
Sign up to set email alerts
|

Causes for 30‐Day Readmission following Transsphenoidal Surgery

Abstract: Overall, the rate of 30-day readmission following endoscopic pituitary surgery is low. However, common causes of readmission do add significant cost to the overall care of this patient population. Special attention to surgical technique to prevent epistaxis and cerebrospinal fluid rhinorrhea, as well as multidisciplinary team management to avoid postoperative endocrine dysfunction, is critical to minimize these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
7
42
0
Order By: Relevance
“…210 In 2012, Kassin et al 3 analyzed 1442 patients undergoing general surgical procedures and found a readmission rate of 11.3%. Any postoperative complication had the greatest association with 30-day readmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…210 In 2012, Kassin et al 3 analyzed 1442 patients undergoing general surgical procedures and found a readmission rate of 11.3%. Any postoperative complication had the greatest association with 30-day readmission.…”
Section: Discussionmentioning
confidence: 99%
“…610 The consensus among surgical data is that postsurgical complications are most greatly associated with increased risk of readmission following surgery, but socioeconomic factors and patient comorbidities also have a significant effect. 210 However, data on the 30-day revisit rate specifically relating to facial plastic surgical procedures, including septorhinoplasty, are still lacking.…”
mentioning
confidence: 99%
“…Complications after EESBS such as CSF leak can lead to costly readmissions and disrupt patient recovery, yet routine intraoperative practices such as the use of LDs and reconstructive techniques have not yet been standardized. Meta‐analyses have not shown any significant decrease in postoperative CSF leak when an LD was used in routine pituitary surgery .…”
Section: Discussionmentioning
confidence: 95%
“…The Hospital Readmissions Reduction Program, established through the Affordable Care Act, reduces payments to hospitals with excessive 30‐day readmissions . There have been several publications in the surgical literature exploring factors associated with increased readmission rates, and the consensus among this data is that surgical complications have the greatest association with 30‐day readmissions, but socioeconomic factors and patient comorbidities also have a significant impact . Although we did not find an association between readmission and socioeconomic factors, the presence of an outpatient tracheostomy‐related complication carried the greatest odds of readmission on multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%